Diversified Development : Making the Most of Natural Resources in Eurasia - Gill, Indermit S. (Washington, DC: World Bank, 2014)
This report is about the twelve countries of the former Soviet Union (Eurasia). About 85 percent of the region’s economic output is in six resource-rich economies. Today, 85 percent of Eurasia’s 280 million people are no longer poor. But academics who study resource-based economies debate whether these countries are cursed or blessed. And Eurasia’s policymakers long for the day when their economies are less extractive and more innovative. These observations prompt questions: Are resources a blessing or a curse? If it is one of these things, what would make it into the other? How much should Eurasia try to diversify their exports and economies away from natural resources? Are there ways to make Eurasian economies both extractive and innovative? The answers: a large majority of Eurasia’s people should consider themselves blessed. To make sure that this blessing does not become a curse, Eurasian economies have to become efficient—more productive, job-creating, and stable. But efficiency is not the same as diversification: there is little evidence that more concentrated economies have slower productivity growth, fewer jobs, or much more economic volatility. Governments need to worry less about the composition of exports and production and more about asset portfolios—natural resources, built capital, and economic institutions. They have much to do. Eurasia’s portfolios are heavy in tangibles like oil and gas and roads and railways and light in intangibles such as the institutions for managing resource earnings, providing social services, and regulating enterprise. But tangibles are not what distinguish success from failure—investments in intangibles, early in their development, have made some resource-rich countries both extractive and innovative.